Association of Conjunctivitis through Microflora in Optical Lenses Users - Sohail Zia, Muhammad Usman Arshad, Aunaza Maqbool, Rabia Sharif Bhatti, Zamir Iqbal, Masud-Ul-Hassan (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To find the association of conjunctivitis through microflora in optical lenses users. Study design: Cross sectional study Place and duration of study: Department of Ophthalmology, Pakistan Railways Hospital, Islamic International Medical College, Rawalpindi from 1st January 2021 to 30th June 2021. Methodology: Forty patients were enrolled. Patient’s clinical symptoms, features were examined for conjunctivitis and slit lamp examination was also followed. Swab cultures from optical lenses were taken for conducting various agar v=based cultures for identifying microorganisms presence. Results: There were more males than females with mean age were 25±4.5 years. Clinical examination presented dryness in eyes as highest percentage. The anti-microbial sensitivity showed highest susceptibility pattern for resistance of ampicillin. Various bacterial types showed that highest frequency of Micrococci as 47.5%. Conclusion: A Robust association of conjunctivitis through microflora was found optical lenses users.